Les textiles dans les tombes gauloises à dépôt de crémation en vase métallique : usages pratiques, mises en scène et perspectives anthropologiques (seconde moitié du vie s.-ve s. av. J.-C.) - Elsa Desplanques (Gallia)
The deposit of cremated remains in a metal vessel is a funerary practice adopted by a limited number of individuals belonging to the elite members of protohistoric European societies (Verger 1995b; Desplanques 2022). Used as ossuaries, the vessels are mostly made of copper alloys. This funerary practice was used over a period of about a thousand years, between the 14th c. BC and the 3rd c. BC, across an immense geographical area, covering part of present-day Europe, from Scandinavia to Cyprus and Western to Central Europe. Between the second half of the 6th and the 5th c. BC, a shift occurred at the European scale. The phenomenon of metal vase cremation deposits appeared, or rather reappeared, suddenly and markedly, for about 50 or even 100 years, particularly in Gaul, the Greek world, Northern Europe and the Italian peninsula. Textiles were frequently present among the burnt bones of these metal ossuary assemblages. The transition from the Late Hallstatt to the Early La Tène period is particularly interesting considering the use of textiles in tombs, as their presence is attested to for a significant number of cases. Gallic ossuaries are particularly well documented in this regard. Although the use of cloth in this context has been regularly attested to since the 19th c., particularly for Gallic and Rhenish sites, the description of this material remained brief and disparate. A review was necessary in order to quantify and qualify the fragments (number, nature, arrangement) in relation to the ossuary and burnt bone assemblages, as well as to then attempt to understand the way in which these fabrics were used within funerary ritual. In an attempt to identify possible differences or similarities, cloth fragment arrangements within Gallic ossuaries, as well as technical characteristics of the fabrics selected for burial, were compared with contemporary data available for other groups of metal vase cremation deposits, notably the Germanic, Greek and Italic groups. Analysis of the textile fragments suggests uses that were both homogeneous in their overall pattern, but varied in the details. The large majority of fragments were found within the ossuaries, in direct contact with the remains: they might have been used to wrap the bones or have been folded and the bones laid over top. The fragments found outside the ossuaries demonstrate more diverse types of use: the fabrics may have served to cover, wrap, or dress the cinerary or they may have simply been tied, as ribbons, around the deposit. All of these practices can be compared with those observed on earlier or contemporary funerary urns. The remarkable permanence of some of the fabric, highlights both their cultural and symbolic importance. Metal vessels used as ossuaries may have travelled long distances before being buried. Gestures involving cloth may be the result of specific local transmissions or learning. They may also be the result of transpositions from one society to another, of social, intellectual, cultural and personal choices. The use of fabrics in burials lead to the identification of shared codes of practice that Justin Jennings sees as one of the characteristics of globalised behaviour (Jennings 2017, p. 12-14). Furthermore, the Gallic textiles found in cremation deposit burials, and within metal vessel containers are among the most beautiful archaeological finds. The quality of the textiles is attested to by technical analysis, which indicates the use of worked materials and decorative additions. This study of the cloth fragments also indicates that while certain gestures may have been adopted in the burials, it seems that the communities specifically selected locally produced fabrics or imported fabrics whose technical and visual characteristics were consistent with local production. It is likely that personal and sentimental criteria played a role in the choice of fabric: the fabric embodies the identity of its wearer, but also of its creator. The display of this fabric at the funeral would have symbolised the relationship between the deceased and their community, as well as their social rank and ethnic origin. Within the framework of highly regulated and ritually established practices, the aim is to reflect on the modalities of implementation and the meaning of the manifest discourse, expressed by the gestures linked to textiles in the funerary contexts of ancient societies. These reflections are focused on the textiles potentially visible during funerals, those present on the exterior of the urns. Considerations of the anthropological interpretation of textile use are based on Greek written sources prior to or contemporary with the 5th c. BC, as well as later Irish and Welsh mythological sources. The aim is not, of course, to draw direct comparisons, but rather to highlight the strength of a potential symbolic system based on textile materials. While the practical aspect of the use of fabric in burials for the material protection of bone remains and metal objects at risk of corrosion should not be ignored, it cannot explain the continuity and coherence of the gestures observed over a period of nearly 1,000 years. Death represents the opportunity for a construction of the other, who has become dangerous if not enigmatic: it is a moment dedicated to specific discourses, gestures and staging, the identification of which reveal avenues of interpretation related to our understanding and representation of this natural phenomenon. Neither leaving visible nor hiding represent trivial choices: the available ancient sources underscore the close connection between seeing and not seeing, and between life and death. In ancient texts and iconography, death is often described as an opaque material or nebulous envelope. Whatever its nature, it blinds the condemned, rendering them invisible to the eyes of the living or submerging them in darkness (Vernant 1985). The fabrics thus appear to intervene in a similar staging of the representation/dissimulation dialectic. Arranged on or within the funerary materials, they lead to the breaking of the visual communication channel between the funeral participants and the deceased. The covering or wrapping expresses the irreversibility of the departed’s death, but also of the objects assigned to them (Augstein 2018, p. 82). The spectator’s view is directed outwards, towards the other living members of the ceremony, while the deceased is confined, dissimulated behind the woven boundary. The funeral spectator thus possesses both the literal and metaphorical vision, since by truly witnessing the action of death, they apprehend it, know it and master it. Furthermore, the empty garment is a particularly effective image to illustrate the physical disappearance of an individual, which in the case of cremation is a supervised disappearance. Moving cloth covers a living body, but in the grave it embodies the absence of the deceased. The anxiety produced by emptiness and the invisibility of the deceased is thus soothed by a visual reconstruction. Whatever the symbolic and social messages expressed by the covering or packaging of these objects, fabric was likely a very effective vector. The sensory role of textiles appears obvious: shapes, colours, textures, drapes and possible scented products are all elements of a visual, auditory, tactile and olfactory communication system. The structural properties of textiles make them ideal descriptive elements, that help to structure the visual and verbal narrative. Archaeological and literary comparisons open up enriching avenues of reflection concerning the polysemy of these funerary ensembles. The choices highlighted by these European-wide analyses and comparisons underscore the fact that individuals embraced a practice and imbued it with a meaning that was both generic and well-rooted in local cultural and religious contexts.